Solve the system of two equations using elimination with multiplication. 4x−6y=−48 −2x+4y=30

1 answer

To solve the system of equations using elimination with multiplication, we need to multiply one or both of the equations by a constant so that when we add or subtract the two equations, one of the variables will be eliminated.

To eliminate the x-term, we can multiply the second equation by 2:
(2)(-2x + 4y) = (2)(30)
This gives us:
-4x + 8y = 60

Now we can add this equation to the first equation in order to eliminate the x-term:
4x - 6y + (-4x + 8y) = -48 + 60

This simplifies to:
2y = 12

Now we can solve for y by dividing both sides of the equation by 2:
2y/2 = 12/2
y = 6

Substituting this value of y back into one of the original equations, we can solve for x.
Using the first equation:
4x - 6(6) = -48
4x - 36 = -48
4x = -12
x = -3

Therefore, the solution to the system of equations is x = -3 and y = 6.